Improving primary Nbss morphology and fracture toughness in hypoeutectic Nb-Si-Ti ternary alloy by ultrasonic treatment. (15th December 2021) - Wang, Shu; Wang, Qi; Chen, Ruirun; Chai, Yue; Jin, Yinling; Su, Yanqing
Graphical abstract: Highlights: Nb-Si alloys treated by ultrasound were proposed and investigated for the first time. The acoustic streaming and cavitation effects promoted the primary niobium solid solution phases coarsened and spheroidized. The ultrasound treatment accelerated the sluggish eutectoid reaction occurrence. The fracture toughness of Nb-16Si-22Ti alloy (treated by ultrasound of 200 s) was improved by 69.16%. Abstract: Nb-Si ultra-high temperature alloys have been a hot topic in aviation materials, but low fracture toughness limits the application. Ultrasound treatment has a significant advantage on the grain refinement and properties improvement, successfully induced into hypoeutectic Nb-Si-Ti ternary alloys to improve primary morphology and fracture toughness. In this work, Nb-16Si-22Ti alloy was treated by ultrasound of 0 s, 80 s, 120 s, 160 s and 200 s. Meanwhile, the coupled physical fields were simulated in Comsol Multiphysics to reveal the mechanism of ultrasonic action. Results show that γ-Nb5 Si3 appears with ultrasound induced, and the solidification path is close to the equilibrium transition. Primary Nbss phases were coarsened and spheroidized after ultrasound treatment, and fracture toughness improved by 69.16%. Simulation results show that the strong acoustic active zone is at the height of 15 mm in the ingot, with maximum sound pressure of 36.3 MPa. The high sound pressure can break dendrites. Maximum fluid velocity reaches 0.03 m/s in the longitudinal section and 0.02 m/s in the transversal section with several circulations. Acoustic streaming and cavitation effects break dendrites and spheroidize Nbss phase, benefit to elements distribution uniformly, equilibrium transition and fracture toughness improvement.